Bonhoeffer's Christocentric theology and fundamental debates in environmental ethics - Heuvel, Steven C. van den (Eugene, Oregon Pickwick Publications, 2017)
There is widespread understanding of the close connection between religion and the ecological crisis, and that in order to amend this crisis, theological resources are needed. This monograph seeks to contribute to this endeavor by engaging the theology of Dietrich Bonhoeffer. His theology is particularly suitable in this context, due to its open-ended nature, and to the prophetic and radical nature of the questions he was prepared to ask--that is why there are many other attempts to contextualize Bonhoeffer's theology in areas that he himself has not directly written about. In this monograph, Steven van den Heuvel first of all addresses the question of how to translate Bonhoeffer's theology in a methodologically sound way. He settles on a modified form of the general method of correlation. Then, secondly, van den Heuvel sets out to describe five major concepts in Bonhoeffer's work, bringing these into critical interplay with discussions in environmental ethics and eco-theology. In making the correlations he thoroughly describes each concept, situating it in the historic and intellectual background of Bonhoeffer's time. He then transposes these concepts to contemporary environmental ethics, describing what contribution Bonhoeffer's theology can make. - back of book
Introduction -- Care for the natural in light of Christ-reality -- Nature in relation to Christ -- Human beings as distinctive parts of nature -- Human beings as masters and lovers of nature -- Bonhoeffer's theology of responsibility and the social dimension of environmental ethics -- Conclusion.
Revision of author's thesis (Ph. D.)--Evangelische Theologische Faculteit, 2015
Includes bibliographical references (pages 275-300) and indexes
Keywords: Bonhoeffer, Dietrich -- 1906-1945; Bonhoeffer, Dietrich -- 1906-1945 -- Ethics; Jesus Christ -- Person and offices; Ecology -- Religious aspects -- Christianity; Ecology; Bonhoeffer, Dietrich; Bonhoeffer, Dietrich; Jesus Christ